Antifungal Activity of Lavandula angustifolia Essential Oil against Candida albicans: Time-Kill Study on Pediatric Sputum Isolates - Stefan Mijatovic; Jelena Antic Stankovic; Ivana Colovic Calovski; Eleonora Dubljanin; Dejan Pljevljakusic; Dubravka Bigovic; Aleksandar Dzamic (Molecules, 2022)
The aim of our study was to determine the susceptibility of 15 Candida albicans sputum isolates on fluconazole and caspofungin, as well as the antifungal potential of Lavandula angustifolia essential oil (LAEO). The commercial LAEO was analyzed using gas chromatography-mass spectrometry. The antifungal activity was evaluated using EUCAST protocol. A killing assay was performed to evaluate kinetics of 2% LAEO within 30 min treatment. LAEO with major constituents’ linalool (33.4%) and linalyl acetate (30.5%) effective inhibited grows of C. albicans in concentration range 0.5–2%. Fluconazole activity was noted in 67% of the isolates with MICs in range 0.06–1 µg/mL. Surprisingly, 40% of isolates were non-wild-type (non-WT), while MICs for WT ranged between 0.125–0.25 µg/mL. There were no significant differences in the LAEO MICs among fluconazole-resistant and fluconazole-susceptible sputum strains (p = 0.31) and neither among caspofungin non-WT and WT isolates (p = 0.79). The 2% LAEO rapidly achieved 50% growth reduction in all tested strains between 0.2 and 3.5 min. Within 30 min, the same LAEO concentration exhibited a 99.9% reduction in 27% isolates. This study demonstrated that 2% solution of LAEO showed a significant antifungal activity which is equally effective against fluconazole and caspofungin susceptible and less-susceptible strains.